1998
DOI: 10.1016/s0735-1097(98)00345-3
|View full text |Cite
|
Sign up to set email alerts
|

New Doppler echocardiographic applications for the study of diastolic function

Abstract: Doppler echocardiography is one of the most useful clinical tools for the assessment of left ventricular (LV) diastolic function. Doppler indices of LV filling and pulmonary venous (PV) flow are used not only for diagnostic purposes but also for establishing prognosis and evaluating the effect of therapeutic interventions. The utility of these indices is limited, however, by the confounding effects of different physiologic variables such as LV relaxation, compliance and filling pressure. Since alterations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
590
6
26

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 903 publications
(646 citation statements)
references
References 58 publications
18
590
6
26
Order By: Relevance
“…By contrast, Ea, E/Ea and LAVI presented unidirectional changes with worsening LV diastolic function. 14,[19][20][21][22][23][24] This pseudonormal phenomenon as LV diastolic dysfunction increases in E/A but not in Ea, E/Ea and LAVI may explain the different results between E/A and Ea, E/Ea and LAVI in the present study. In addition, previous studies found that decreased Ea and increased E/Ea and LAVI were correlated with LV diastolic dysfunction.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…By contrast, Ea, E/Ea and LAVI presented unidirectional changes with worsening LV diastolic function. 14,[19][20][21][22][23][24] This pseudonormal phenomenon as LV diastolic dysfunction increases in E/A but not in Ea, E/Ea and LAVI may explain the different results between E/A and Ea, E/Ea and LAVI in the present study. In addition, previous studies found that decreased Ea and increased E/Ea and LAVI were correlated with LV diastolic dysfunction.…”
Section: Discussioncontrasting
confidence: 64%
“…In addition, previous studies found that decreased Ea and increased E/Ea and LAVI were correlated with LV diastolic dysfunction. [19][20][21][22][23] The present study demonstrated that rbPEP/rbET had an important impact on the relationship between baPWV and LV diastolic function, as indicated by Ea, LAVI and E/Ea values. Patients in group 1 and group 4 had relatively good and poor LV diastolic function, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…Based on the current findings, 3D three-directional VE MRI with retrospective valve tracking not only provides more accurately transmitral flow volumes and regurgitation fraction as compared to 2D one-directional VE MRI, but the 3D VE MRI approach also better discriminates restrictive transmitral flow when Doppler echocardiography is used as the reference standard. This is important for the clinical evaluation of symptoms, optimization of therapy, and prediction of prognosis in heart failure patients (15,20).…”
Section: Discussionmentioning
confidence: 99%
“…First, because mitral annulus velocity measured by DTI is relatively load independent, it seems particularly useful in markedly altered ventricular loading conditions such as valvular regurgitation. 8,9 Second, conventional Doppler techniques derive their information on myocardial function from blood flow velocity, but DTI directly measures indices of myocardial function from myocardium itself. 17 Therefore, DTI indices have been shown to have good correlation with invasive markers for ventricular systolic and diastolic function, such as dP/dt max and time constant of relaxation (tau).…”
Section: Doppler Tissue Imaging and Pulmonary Venous Reversal Flow Vementioning
confidence: 99%
“…8 Because it is relatively load independent, it has a clear advantage over conventional Doppler indices for evaluating LV function. [8][9][10] Therefore, the present study was performed using DTI to determine the echocardiographic parameters that have an influence on exercise capacity in patients with chronic MR.…”
Section: Introductionmentioning
confidence: 99%